Fabrication of a white electroluminescent device based on bilayered yellow and blue quantum dots - Kim, Jong-Hoon; Lee, Ki-Heon; Kang, Hee-Don; Park, Byoungnam; Hwang, Jun Yeon; Jang, Ho Seong; Do, Young Rag; Yang, Heesun (ROYAL SOC CHEMISTRY, 2015)
Until now most work on colloidal quantum dot-light-emitting diodes (QLEDs) has been focused on the improvement of the electroluminescent (EL) performance of monochromatic devices, and multi-colored white QLEDs comprising more than one type of QD emitter have been rarely investigated. To demonstrate a white EL as a result of color mixing between blue and yellow, herein a unique combination of two dissimilar QDs of blue-CdZnS/ZnS plus a yellow-emitting Cu-In-S (CIS)/ZnS is used for the formation of the emitting layer (EML) of a multilayered QLED. First, the QLED consisting of a single EML randomly mixed with two QDs is fabricated, however, its EL is dominated by blue emission with the contribution of yellow emission substantially weaker. Thus, another EML configuration is devised in the form of a QD bilayer with two stacking sequences of CdZnS/ZnS//CIS/ZnS QD and vice versa. The QLED with the former stacking sequence shows an overwhelming contribution of blue EL, similar to the mixed QD EML-based device. Upon applying the oppositely stacked QD bilayer of CIS/ZnS//CdZnS/ZnS, however, a bi-colored white EL can be successfully achieved by means of the effective extension of the radiative excitonic recombination zone throughout both QD EML regions. Such QD EML configuration-dependent EL results, which are discussed primarily using the proposed device energy level diagram, strongly suggest that the positional design of individual QD emitters is a critical factor for the realization of multicolored, white emissive devices.
Keywords: LIGHT-EMITTING-DIODES; INP-AT-ZNSES; HIGHLY EFFICIENT; PERFORMANCE; NANOCRYSTALS